ValBioTecCynara – Economic Enhancement Cynara cardunculus: Natural Variability and its Biotechnological Applications - Conceição, Cristina (2019)
ValBioTecCynara aims to address the natural C cardunculus L genetic, molecular, morphologic, and biochemical variabilities, as a combined strategy to identify individuals with certain and specific required profiles C cardunculus L is used as a coagulant for cheesemaking where the respective use is mandatory in certain cheeses benefiting from Protected Designation of Origin ( 1 The potential of 15 different C cardunculus L natural occurring populations within Alentejo region (south of Portugal), were evaluated on flower technological properties, being three of them studied regarding chemical, rheological and sensorial characteristics within the three PDO Alentejo cheeses Évora Serpa and Nisa A significance variability on flower technological properties was found, based on milk clotting activity, gel firmness, micellar aggregation rate and proteolytic activity and it was possible to identify 5 different groups of C cardunculus L populations 2 The action of coagulant populations was specific according the cheese matrix Nevertheless, a common pattern of cheese proteolysis, rheology and sensory characteristics was verified, allowing to highlight the cheeses manufactured with two of the three C cardunculus L populations Proteolysis was more intense in early stages of ripening, influenced by cheese moisture content and raising to caseins fractions, β caseins were less susceptible to proteolysis than α S caseins with influence in cheese sensory characteristics These results have a very stimulating uses concerning specific target, such as uncertainty in the cheese manufacture, contributing to the incentive of the cheese production systems promoting the milk production of small ruminants Keywords Cynara cardunculus L proteases milk PDO Évora, Serpa, Nisa cheeses 1 Conceição C, Martins P, Alvarenga N, Dias J, Lamy E, Garrido A, et al Cynara cardunculus Use in Cheesemaking and Pharmaceutical Applications In Koca N Technological Approaches for Novel Applications in Dairy Processing InTechOpen 2018 http :://dx doi org/ 10 5772 /intechopen 76530 2 Gomes S, Belo AT, Alvarenga N, Dias J, Lage P, Pinheiro C, et al Characterization of Cynara cardunculus L flower from Alentejo as a coagulant agent for cheesemaking Int Dairy J 2019 91 178 84 This project was funded by European Regional Development Fund ( ValBioTecCynara (ALT 20 03 0145 FEDER 000038 Economic valorisation of Cardoon Cynara cardunculus study of natural variability and biotechnological applications The authors acknowledge FCT for PhD grant to Teresa Brás (SFRH/ 110969 2015